Long-term consequences of short-term precipitation shocks: Evidence from Brazilian migrant households - Mueller, Valerie; Osgood, Daniel Edward (Wiley, 2009)
We find that large short‐term precipitation shocks damage the long‐term income of households that have permanently migrated from rural to urban areas. This outcome is consistent with the behavior of credit‐constrained rural households who are willing to accept lower long‐term income in urban areas following the depletion of their productive assets during an adverse shock. Our empirical evidence suggests that there may be a link between large precipitation shocks in rural areas and urban poverty. Further exploration is warranted on the mechanisms by which natural disasters cause these long‐term losses.